OC-014 Clinical and Endoscopic Improvement following Hemopoietic Stem Cell Transplantation vs Mobilisatiion alone in Crohn'S Disease. (4th June 2013) - Hawkey, C; Allez, M; Ardizzone, S; Clark, L; Columbel, J-F; Danese, S; Farge-Bancel, D; Labopin, M; Lindsay, J; Norman, A; Onida, F; Ricart, E; et al.
Abstract : Introduction: The Autologous Stem Cell Transplantation International Crohn's Disease (ASTIC) Trial is a randomised controlled trial co-sponsored by ECCO and EBMT and funded by the Broad Foundation that investigates immunoablation and hemopoietic stem cell transplantation (HSCT) in Crohn's disease (CD) over 1 year: all patients will have reached this endpoint by April 2013. Methods: Patients with impaired quality of life due to active CD, despite ≥ 3 immunosuppressive agents all underwent mobilisation (iv cyclophosphamide 4 gm/M2 over 2 days then filgrastim10µ/kg/day) before randomisation to immediate (1 month) or delayed (13 months) HSCT. The conditioning regime was iv cyclophosphamide 50mg/kg per day for 4 days, anti-thymocyte globulin 2.5 mg/kg/day and methyl prednisolone 1mg/kg on days 3–5. The bone marrow was reconstituted by infusion of an unselected graft of 3–8 × 106/kg CD34 +ve stem cells. Clinical (CDAI), endoscopic (SES-CD) quality of life and safety data are compared 1 year after mobilisation alone or after mobilisation and HSCT. Results: As of Jan 2013, data are available on 34/45 patients. Following mobilisation and HSCT, the CDAI fell from 317 (median, IQR 244–407) to 157 (71–246, n = 17) vs 351 (313–446) and 298 (220–370, n = 17) with mobilisation alone. The aggregate lower GI SES-CD score was 13.0 (8.5–24.5) before and 3.0 (1.5–10.0) after HSCT compared to 13.0 (6.5–15.5) before and 6.5 (3.5–17.8) after mobilisation alone. Over the whole study to end 2012 there were 62 SAEs in 19 patients randomised to early transplantation (3.3 per patient) and 58 in 18 patients randomised to delayed transplantation (3.2 per patient). One patient died following HSCT. Final results of the study will be available to be presented for the first time at BSG 2013. Conclusion: Immunoablation and HSCT appears to be an effective treatment for CD that may substantially reduce endoscopic evidence of disease but incurs significant toxicity. The final results of the trial will allow a rational evaluation of the effectiveness and safety of HSCT to be discussed at BSG 2013. Disclosure of Interest: None Declared